Constructing Regional Image through Local Media: The Role of Ajatappareng Television Image Partners in Sidrap Regency - Zul Inayah Yusuf; Irwan Irwan; Haeruddin Syarifuddin (Dinasti Publisher, 2025)
This study investigates how a local media outlet constructs the public image of Sidenreng Rappang Regency through its broadcasting practices, narrative choices, and representations of local identity. The research aims to explain the ways in which MCTV Ajatappareng frames regional development, cultural values, and tourism potential, while also examining the dynamics of media-government interaction in shaping these narratives. Employing a qualitative single case study design, data were gathered through in-depth interviews, participatory observation, and documentation of broadcast archives and news reports, then analysed using thematic procedures. The findings show that regional image construction emerges through development-oriented storytelling, the reinforcement of cultural representation, and the promotion of local potential. Media-government relations take the form of semi-institutional collaboration that influences information flow and content production. The construction of regional image is strengthened by access to information and media proximity to the audience, yet constrained by limited human resources and the absence of a structured regional communication roadmap. The study introduces the Media-Governance-Image Nexus as a conceptual model that illustrates the interdependent roles of media, government, and public perception. The results contribute to theoretical discussions on communication governance and provide practical insights for enhancing collaborative public communication strategies.